2018
DOI: 10.24273/jgeet.2018.3.4.2088
|View full text |Cite
|
Sign up to set email alerts
|

Festivals and deterioration of aquatic environment: A case study of Idol immersion in Tapi River, India

Abstract: In the civil society different festivals are celebrated, these are the integral part of human life and many of festivals are religious, seasonal change and culturally important. The present study elucidated environmental impact of Ganesh idol immersion on water quality of Tapi River and for this purpose water samples were collected during different durations (pre immersion, during immersion and post immersion) from selected sampling stations or idol immersion points of Tapi River. The important water quality p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Idol immersion and pollution load assessment in different water bodies including rivers were studied in different parts of India by Gorain and Paul (2019) in urban lakes (Karnataka), Lokhande (2019) in Gorai Jetty (Maharashtra), Rakshit and Sarkar (2018) in Hooghly River (West Bengal), Sorte et al (2018) in Gandhisagar Lake (Maharashtra), Joshi et al (2017) in Narmada River (Madhya Pradesh), Belsare et al (2017) in Futala Lake (Maharashtra), Sarbari and Pande (2015) in Yamuna River (Delhi), Billore and Dandawate (2015) in Kakerpura Lake (Madhya Pradesh), Patil et al (2014) in Futala Telangkhedi Lake (Maharashtra) and Kaur (2012) in marine and freshwater body (Maharashtra). Similarly, notable study in Tapi River were reported by Bengani et al (2020), Ujjania et al (2018), Jain et al(2018), Sangani and Manoj (2017), Malvia and Vaghani(2016), Ekhalak et al (2015), Gadhia et al (2014) and Malik et al (2012).…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Idol immersion and pollution load assessment in different water bodies including rivers were studied in different parts of India by Gorain and Paul (2019) in urban lakes (Karnataka), Lokhande (2019) in Gorai Jetty (Maharashtra), Rakshit and Sarkar (2018) in Hooghly River (West Bengal), Sorte et al (2018) in Gandhisagar Lake (Maharashtra), Joshi et al (2017) in Narmada River (Madhya Pradesh), Belsare et al (2017) in Futala Lake (Maharashtra), Sarbari and Pande (2015) in Yamuna River (Delhi), Billore and Dandawate (2015) in Kakerpura Lake (Madhya Pradesh), Patil et al (2014) in Futala Telangkhedi Lake (Maharashtra) and Kaur (2012) in marine and freshwater body (Maharashtra). Similarly, notable study in Tapi River were reported by Bengani et al (2020), Ujjania et al (2018), Jain et al(2018), Sangani and Manoj (2017), Malvia and Vaghani(2016), Ekhalak et al (2015), Gadhia et al (2014) and Malik et al (2012).…”
Section: Introductionmentioning
confidence: 66%
“…Therefore, it is considered diversified country for the rituals and cultures where every year different religious activities are gratified at the bank of water resources like ponds, lakes, rivers etc. The Ganesh Chaturthi is the important festival during which idols are worshiped and immersed in nearby water resources that play an important role to deteriorate the water quality and add the pollutant in water resources (Ujjania et al, 2018). People are always excited to celebrate the religious activities and large number of different sized idols 27000 (2010), 30000 (2017) and 60000 (2018) were immersed in Tapi river (Surat) during Ganesh festival (Anon, 1018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation